Abolishing the taboo: President Eisenhower and the permissible use of nuclear weapons for national security - Jones, Brian Madison (Kansas State University, 2008)
As president, Dwight Eisenhower believed that nuclear weapons, both fission and fusion, were permissible and desirable assets to help protect U.S. national security against the threat of international communism. He championed the beneficent role played by nuclear weapons, including both civilian and military uses, and he lauded the simultaneous and multi-pronged use of the atom for peace and for war. Eisenhower's assessment of the role and value of nuclear technology was profound, sincere, and pragmatic, but also simplistic, uneven, and perilous. He desired to make nuclear weapons as available, useful, and ordinary for purposes of national security as other revolutionary military technology from the past, such as the tank or the airplane. He also planned to exploit nuclear technology for a variety of peaceful, civilian applications that he also believed could contribute to national strength. However, Eisenhower did not possess a systematic view of national security in the nuclear age as some scholars have argued. Rather, Eisenhower approached the question of how to defend national security through nuclear weapons with an array of disparate ideas and programs which worked simultaneously toward sometimes divergent objectives that were unified only by a simple conception of national strength. In this effort, Eisenhower occasionally pursued what might seem to be conflicting initiatives, but nonetheless consistently advanced his view that strength through nuclear technology was possible, necessary, and sustainable. Because he believed nuclear technology effectively served his goal to defend national security through strength, Eisenhower sought to reverse the perception that nuclear weapons were inherently dangerous by advocating steadily and consistently for the proper and acceptable use of nuclear technology to contribute to the safety of the republic. He conceived policies such as the New Look, massive retaliation, Project Plowshare, and Atoms for Peace in part to convince the American public and the international community of the U.S.'s genuine desire for peace as Eisenhower simultaneously entrenched atomic and thermonuclear weapons into the American national conscience. Through his efforts, Eisenhower made nuclear weapons and nuclear technology ordinary, abundant, and indispensable to U.S. national security in the twentieth century.
Keywords: Dwight Eisenhower; Nuclear weapons; National strength; Cold War; History, United States (0337)